SPIRITUALITASPOLITIK KAUM SANTRI: (Upaya menghadirkan spiritualitas politik dalam panggung kekuasaan) - Ridho, Achmad Ainur (STQINIS, 2017)
Political spirituality is termenology refer to a concept about substance of religious messasges of politic, consist of political paradigm and political ethic. Political spirituality was be discourse to appear on politic constellation as solution wherever the problems of nation-state caused by image of politic. Politicians as like lose of religious morality control in playing political act in which create anomaly of power. One of chronic epedemies were corruption380that be seriously problem until now.In a concept of political spirituality used be proclaimed by santri as presentation or pesantren to make a color or new constellationof politic in Indonesia.